2023
DOI: 10.3390/ijms24087673
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Integrative Analysis of the Inhibitory Effects of Dipeptides on Amyloid β Peptide 1–42 Polymerization

Abstract: The major pathological feature of Alzheimer’s disease (AD) is the aggregation of amyloid β peptide (Aβ) in the brain. Inhibition of Aβ42 aggregation may prevent the advancement of AD. This study employed molecular dynamics, molecular docking, electron microscopy, circular dichroism, staining of aggregated Aβ with ThT, cell viability, and flow cytometry for the detection of reactive oxygen species (ROS) and apoptosis. Aβ42 polymerizes into fibrils due to hydrophobic interactions to minimize free energy, adoptin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 52 publications
0
0
0
Order By: Relevance
“…Polymerized Aβ42 adopts a conformation in which the backbone atoms are distributed almost in a flat plane, while the Aβ42 monomer is a globular protein, in the MD analysis. Previous molecular docking studies have found that a few dipeptides bonded to the polymerization core of Aβ42, and thus inhibited polymerization [15]. In the present study, a molecular docking experiment between Aβ42 and oligopeptides was carried out.…”
Section: Molecular Docking Of Tripeptidesmentioning
confidence: 89%
See 4 more Smart Citations
“…Polymerized Aβ42 adopts a conformation in which the backbone atoms are distributed almost in a flat plane, while the Aβ42 monomer is a globular protein, in the MD analysis. Previous molecular docking studies have found that a few dipeptides bonded to the polymerization core of Aβ42, and thus inhibited polymerization [15]. In the present study, a molecular docking experiment between Aβ42 and oligopeptides was carried out.…”
Section: Molecular Docking Of Tripeptidesmentioning
confidence: 89%
“…In this study, a molecular dynamics analysis was used to examine both the binding free energy in protein complexes as well as the time-dependent changes in the locations of the heavy atoms of the ligands attached to Aβ42. We recently published an article [15] in which we proposed thermodynamic mechanisms and a possible pathway for Aβ42 aggregation. Folding and aggregation were driven by a system's free energy.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations